A TOXICOLOGICAL ANALYSIS OF THE RESIDUES OF PESTICIDE ON LADY FINGER (ABELMOSCHUS ESCULENTUS) BEFORE AND AFTER DHAVAN BY HARIDRA-JAL - Rathor, *Sangeeta; Sharma, Anita (International Journal of Ayurveda and Pharma Research, 2016)
The concentration of various pesticide were well below the established tolerances but continuous consumption of such vegetables even with moderate contamination level can accumulate in the receptors body and may prove fatal for human population in the long-term. Along with the green revolution uses of pesticides including profenofos is increased and increasing day by day. The pesticide residue including profenofos in all edible things including okra is crossing the maximum permissible limit and arising a big long term hazards in human beings due to inorganic agriculture. Okra is sprayed with a number of pesticides for greater yield, ripening or storage. Commonly used methods for cleaning this vegetable are washing with tap water, warm water, or salt water. In Ayurveda some Vishaghna dravya are mentioned. So, the study was planned to observe whether the toxic residues are nullified or reduced in the solution of the Vishaghna dravyas. The drug Haridra selected for this analytical study of pesticide residue is one of important drug mention in Ayurveda. Aacharya Charak has included 10 herbs in Vishaghna Mahakashaya including Haridra. So it was taken as a Dhavan dravya.